Creative activities for young children - Mayesky, Mary. (Albany, N.Y. : Delmar, 1998)
Theories relating to child development. Theory into practice.
Keywords: Education; Child development; Activity programs; Early childhood education; Child development -- United States; Education -- Creative activities and seat work; Early childhood education -- Activity programs -- United States